(untitled) (IAHS Medical Journal, 2024)
Background: Admission Cardiotocography (CTG) a noninvasive procedure, is used to indicate the state of oxygenation of the fetus on admission into the labor ward. This study is performed to assess the association of admission CTG findings with feto-maternal outcome at a tertiary health facility in Bangladesh. Materials and methods: A prospective, observational study of 50 pregnant women who were admitted into the labor ward with singleton live pregnancies in Bangabandhu Sheikh Mujib Medical University. Information on the demographic characteristics, obstetrics and medical history, admission CTG tracing and neonatal outcome was obtained using a structured data collection form. Data were analyzed using the SPSS software version 20.0 with the level of significance set at p< 0.05. Results: The admission CTG findings were normal in 72% and abnormal in 28% of the women. The occurrence of low birth weight, asphyxiated neonates and Special Care Neonatal Unit (SCANU) admission was significantly more frequent among those with abnormal admission CTG results compared with normal results (p<0.001 for each). The incidence of cesarean delivery was more common when the CTG findings were abnormal, whereas all women with normal CTG result had a vaginal delivery (p<0.001). Conclusion: Admission CTG was effective in identifying fetuses with a higher incidence of perinatal asphyxia. Neonatal outcome such as low birth weight, APGAR score and SCANU admission was significantly associated with pathological CTG findings. In the absence of facilities for further investigations, prompt intervention for delivery should be ensured if admission CTG is pathological. IAHS Medical Journal Vol 7(1), June 2024; 50-53